Serum Direct Bilirubin as a Biomarker for Breast Cancer - Hu, Jinxi; Cai, Yangjun; Chen, Yijun; Zhu, Xiaoli (Breast cancer targets and therapy, 2024)
The role of serum total bilirubin (TB) in cancer has been a subject of controversy, as has the role of its subtypes, particularly serum direct bilirubin (DB). The aim of the present study was to investigate the association between serum DB levels and breast cancer, as well as to assess the diagnostic utility of serum DB in breast cancer. A total of 5299 patients diagnosed with breast cancer for the first time at Taizhou Hospital of Zhejiang Province were included in the study, and 10028 healthy physical examination subjects were included as healthy controls. Logistics regression was used to investigate the relationship between serum DB and breast cancer, and the value of serum DB in the diagnosis of breast cancer was assessed by means of receiver operator characteristic (ROC) curve analysis. The serum DB concentration in the breast cancer group was significantly higher than the healthy controls ( < 0.001). Multivariate logistic regression results show that serum DB was an independent risk factor for breast cancer (odds ratio [OR]=4.504, 95% confidence interval [CI]: 4.200-4.831). Subjects with a serum DB concentration in the fourth quartile had a higher risk of breast cancer occurrence compared to those in the first quartile after adjusting for age (OR = 7.155, 95%CI: 6.474-7.907). The optimal cut-off value of serum DB for diagnosing breast cancer was determined to be 2.75 μmol/L, with an area under the curve (AUC) of 0.712 (95% CI: 0.703-0.722). This value exhibited good specificity (77.0%) and negative predictive value (77.8%). Serum DB was identified as a risk factor for breast cancer, demonstrating good diagnostic potential for the disease. These findings suggest that serum DB could serve as a promising serum molecular marker for breast cancer.